Training of Ambiental Educators (FEA) in the Cultivando Água Boa (CAB) Program: collective and subjective constructions (Práxis Educativa, 2024)
The aim of the article is to investigate the occurrence of ecological subjects from the environmental education process put in place at the Formação de Educadores Ambientais (FEA) [Training of Environmental Educators], an integral part of the Cultivando Água Boa (CAB) Program [Cultivating Good Water] of Itaipu Binational. The study is qualitative, anchored in bibliographic, documentary and field research, which was carried out from observations and interviews. The data were organized into two categories of interdependent analysis: collective construction and construction of the subject. It concludes that FEA and CAB contribute to the formation of subjects who articulate community environmental governance processes, because they form a social network, allowing exchanges, dialogues, motivation and boosting socioenvironmental actions in the local contexts. The environmental educator trained by FEA is the main articulator of a community environmental governance process, as it involves other people in the network of relationships that seeks sustainability in the territory of the river basin.Keywords:  Environmental education. Training. Experience.